Apparently we have human rights to health? Health and human rights frameworks of people with disabilities in Victoria. Issue 1 (2nd January 2017) - West, Raelene; Ramcharan, Paul; Basser, Lee Ann
ABSTRACT: The extent to which the human rights legislative framework impacts and enables the human right to health for people with disability in Victoria, Australia is contentious. We utilised a human rights monitoring tool developed by Disability Rights Promotion International (DRPI) to explore the understanding and utilisation of this human rights framework by people with disabilities in Victoria. The qualitative element of the research involved completion of 75 in-depth interviews that were thematically analysed in order to draw findings. The interviews conducted were based upon principles and themes related to key human rights articles of the United Nations Convention of Rights of People with Disabilities (CRPD). In this paper we focus on one aspect of the qualitative data obtained from in-depth interviews related to the right to health and the related legislative human rights frameworks for people with disabilities. The findings support the view that human-rights-based interventions do not appear to be providing substantial mechanisms for positive change or protections within the health landscape for people with disabilities, with participants rarely engaging with the human rights framework in addressing human rights breaches.